1999
DOI: 10.1021/ic980862p
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Metallacycles by Oxidative Addition of Sn−S, Sn−Se, Sn−Te, and Ge−Te Containing Precursors to Platinum(II)

Abstract: The first metallacycles formed by oxidative addition of tin-sulfur, tin-selenium, tin-tellurium, and germanium-tellurium bonds to platinum(II) are reported. In particular, the ring compounds [(R(2)SnE)(3)], where R = Me, Ph and E = Se, Te, and the new compound [(Me(2)GeTe)(3)], react with [PtMe(2)(bu(2)bpy)] (bu(2)bpy = 4,4'-di-tert-butyl-2,2'-bipyridine) to give the new organoplatinum(IV) metallacycles [PtMe(2)(R(2)SnE)(2)(bu(2)bpy)] and [PtMe(2)(Me(2)GeTe)(2)(bu(2)bpy)], respectively. The tin-containing meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…We recently found that bis(pyrazol-1-yl)methane modified by organotin groups on the methine carbon may provide unusual reactivity [5]. Furthermore, the oxidative addition of the Sn-E (E = S or Se) bond to low oxidative transition metal complexes is known [19]. Herein, when compounds 1 and 2 were treated with W(CO) 5 (THF) under the same experimental conditions as the reaction of Ph 3 SnCHPz 2 with W(CO) 5 (THF) [5], only known compound 3 was isolated with the decomposition of compounds 1 and 2, no similar reaction taking place.…”
Section: Resultsmentioning
confidence: 99%
“…We recently found that bis(pyrazol-1-yl)methane modified by organotin groups on the methine carbon may provide unusual reactivity [5]. Furthermore, the oxidative addition of the Sn-E (E = S or Se) bond to low oxidative transition metal complexes is known [19]. Herein, when compounds 1 and 2 were treated with W(CO) 5 (THF) under the same experimental conditions as the reaction of Ph 3 SnCHPz 2 with W(CO) 5 (THF) [5], only known compound 3 was isolated with the decomposition of compounds 1 and 2, no similar reaction taking place.…”
Section: Resultsmentioning
confidence: 99%
“…The bond lengths of the selenium-platinum bonds, Pt-Se of 2.4885(5) Å for the germanium containing compound or Pt1-Se1 of 2.4841(6) and Pt1-Se2 2.4917(6) Å for the tin congener arev in the typical range. [39][40][41][42][43][44] The interatomic distances between the selenium and tin, Sn1-Se1 2.4501 (7) and Sn2-Se2 2.4799(7) Å are visibly extended compared to the uncoordinated seleniumtin cluster with a selenium-tin separation of 2.3975(9) Å. 36 The same characteristic is found for the coordinated selenium adduct of germa-closo-dodecaborate.…”
Section: Solid-state Structuresmentioning
confidence: 78%
“…This ligand is expected to act as an unsymmetric multidentate N,N,S or N,N,N 0 ligand for other metal atoms. In addition, the oxidative addition of the Sn-S bond to low-oxidative transition-metal complexes is also observed [18]. However, upon treatment of 7 with W(CO) 5 (THF) under similar experimental conditions as the reaction of 1 with W(CO) 5 (THF), only known complex CH 2 (3,5-Me 2 Pz) 2 W(CO) 4 [17] is isolated with the decomposition of this ligand, and no product of oxidative addition to the tungsten atom is observed.…”
Section: Reaction Of Ligand 1 With 2-pysna (Py = Pyridyl)mentioning
confidence: 93%